Halal Affair Operation Regulations B.E. 2552/C.E.2009 Involve in Thai Halal Products Ecosystem - Dorloh, Sulaiman (Halalsphere, 2021)
Many critics of current Halal Affair Operation Regulation B.E. 2552 (HAOR 2015) from the Muslim consumers concerning Halal products in Thailand. They argue that the HAOR is inadequate to protect Muslim consumers. The absence of clear guidelines and effective monitoring systems concerning Halal products have resulted in Halal products and Muslim consumers receiving inadequate protections, particularly in relation to the abuse of the Halal logos. The HAOR 2015 sets a maximum suspension for one year. This is considered inadequate in preventing irresponsible manufacturers. The paper utilises doctrinal legal analysis and a library based research approach to provide insights in understanding the HAOR 2015 and legal analysis. The paper provides suggestions to enhance the protection of Muslim consumers and upgrade the status of Halal products. The paper also suggests that education should play an important role in promoting HAOR 2015 towards protecting Halal products in Thailand.